Chemical Characteristics of Kepok Banana Bud (Musa Paradisiaca Linn.) Flakes with Variations of Mocaf Flour - Fitriani, Aprilia; Toni, Denna Rianda; Rahmadhia, Safinta Nurindra (Journal Akademik Universitas Swiss German, 2024)
Flakes are food products that have the shape of thin sheets, brownish yellow in color with a practical presentation. Flakes are easy to process and generally consumed for breakfast. Flakes that are rich in dietary fiber and protein can serve as a source of energy while also offering functional advantages. The objective of this study is to generate flakes with elevated levels of dietary fiber and protein by utilizing mocaf and yellow kepok banana bud flour. The use of mocaf flour in the manufacture of flakes intends to improve the fiber content, while the use of yellow kepok banana bud (YKBB) flour aims to boost the protein level. This research was conducted to determine the chemical characteristics of flakes with variations of mocaf flour and KBF. The chemical characteristics include moisture, ash, crude fiber, total protein, lipid, and carbohydrate content. This study used a completely randomised design (CRD) with 2 replications with a ratio of wheat flour, mocaf flour, and YKBB flour as much as the control (20g:0g:0g), F1 (10g:10g:0g), F2 (10g:2.5g:7.5g), F3 (10g:5g:5g) and F4 (10g:7.5g:2.5g). The results showed that the moisture content was 2.43–3.19% w.b., the ash content was 2.55–11.72% d.b., the crude fiber content was 2.17–8.40% d.b., the total protein content was 4.34–7.85% d.b., lipid content 2.46–3.17% d.b., and carbohydrate content was 76.91–87.98% d.b.